Press Control Function of the Surat Kabar Harian (SKH) Rakyat Sultra on the Kendari City Government’s Flood Disaster Management Policy - Faisal, Amir; Fitriadi, Muhammad; Tahir, Muhammad; Alimuddin, Alimuddin; Marhum, Umar (International Journal of Management and Education in Human Development, 2023)
Prolonged, high-intensity rain caused floods that hit almost all regions in Indonesia, and damaged many of the residents' facilities, including government public facilities, such as breaking bridges between one village and another or one sub-district and another. As a result of the flood, quite a few members of the farming community lost their livelihoods because their rice fields were damaged by the flood, and quite a few of them also lost their homes because they were swept away by the flood. Flood disasters not only hit rural areas but also hit almost all urban areas in Indonesia, including Kendari City the capital of Southeast Sulawesi Province. It never escapes flood disasters every time it rains with high intensity. The overflow of two large rivers, namely, the Wanggu River and the Sampara River, who’s downstream is in Kendari City, means that Kendari City never escapes the threat of flood disasters. The problem approach used in this research is a normative juridical approach and an empirical juridical approach. One of the results of research and discussion is that the Surat Kabar Harian (SKH) Rakyat Sultra carries out the press control function, as stated in the Basic Press Law No: 40 of 1999 concerning the Press in the environmental sector, especially in terms of voicing the problem of dealing with floods which continue to hit the people of Kendari City, in every rainy season with high intensity, it is not yet optimal. Even though in other fields such as Education, Business, and Politics it has done its best, because of the special rubrication that has been prepared and one of the conclusions is that the Surat Kabar Harian (SKH) Rakyat Sultra should make environmental issues, especially the problem of handling floods in Kendari City, the main issue. Apart from witnessing the problem of floods continuing to inundate residential areas of residents every rainy season with high intensity, which causes residents' facilities to be damaged due to being submerged in floods, the impact of the floods themselves can be felt directly by media activist journalists, in several sections When there is heavy rain, roads in Kendari City cannot be passed by motorized vehicles because they are flooded with water that reaches the height of an adult's thighs.